Aspects affecting growth of family businesses - Katarína Novotná; Zuzana Lušňáková; Martina Hanová (Economies, 2022)
Family businesses form an inseparable part of each national economy. Therefore, it is necessary to pay significant attention to the aspects that will affect their growth and sustainability in the future. The main aim of this paper is to verify the implementation of key aspects within the entrepreneurial practice of family businesses that considerably affect their growth. Those aspects were identified while processing theoretical input data. On the basis of such knowledge, the research assumptions were determined, and their validity was subsequently verified through the Mann-Whitney U test, the non-parametric Kruskal-Wallis test and the χ2 test of independence. Afterwards, we were able to say that key determinants, such as a formal organisational structure, finance, a constituted family council and a proper code of ethics, have a considerable effect on the growth of family businesses in Slovakia. However, proper legislation that would be a fundamental pillar that family businesses may lean on in any of their operations and activities still needs to be enacted and put into practice.
Keywords: 330; development; family business; growth; management; manager